The Effect of Paitan (Tithonia diversifolia) dose on Growth and Yield of Potato (Solanum tuberosum L.) Granola Purple Flowered Variety - F. Deru Dewanti; Yonny Koentjoro; Sugiarto; Puji Lestari Tarigan (Future Science, 2021)
Potato farming in Jawa Timur currently tends to be oriented towards high production. Increasing the yield of potato quality is by controlling fertilizers and the population. The use of paitan as an organic fertilizer to replace an organic fertilizer is easy and efficient. This study aims to determine the effect of organic fertilizer application on the yield of Granola potatoes (Solanum tuberosum L.). Treatment using a dose of paitan (D) consisted of: D0 = Control (without fertilization), D1 = 120 kg N ha-1 equivalent to 5882 t ha-1 fresh paitan, D2 = 175 kg N ha-1 equivalent to 8,578 t ha-1 fresh paitan, D3 = 230 kg N ha-1 equivalent to 11,273 t ha-1 fresh paitan, D4 = 175 kg N ha-1 equivalent to Urea 380 kg ha-1, P2O 149.76 kg ha-1, K2O 100 kg ha-1. The treatment is given once a week before planting. Parameters observed were plant height and the number of tubers. The results of the study showed that paitan organic fertilizer equivalent to 380 kg N ha-1 was able to produce plant growth and yields that were no different when compared to inorganic fertilizers. In addition, the use of organic fertilizers can preserve the environment for long-term agricultural activities.